Wahai Pengikut Kristus, Mainkanlah Drama yang Mentransformasikan Itu! : Menjawab Peran yang Mentransformasikan dari seorang Kristen bagi Bangsa Indonesia dengan Model Teatrikal dari Kevin J. Vanhoozer - Adrianus Yosia (Indonesian Journal of Theology, 2015)
This article calls Christians to engage in true, transformative action, in Indonesia. To attain to such an alluring provocation, I employ the theatrical ideas of Kevin J. Vanhoozer—namely his thought contribution of "the drama of doctrine"—which I propose finds a suitable complement in Miroslav Volf’s "prophetic religion"- descriptor of Christianity." The combination results in the constructive theopoetic composite I call "transformative drama"—namely, theatrical Christian action that effects change within and leverage impact upon the social locations of the transformative-active Christian.